PENGARUH KESULITAN BELAJAR TERHADAP PRESTASI BELAJAR KOGNITIF PESERTA DIDIK PADA POKOK BAHASAN LAJU REAKSI KELAS XI IPA SMA SANTO PAULUS MANOKWARI - Charlotha Pareang; Nurbayiti La Iki (Universitas Papua, Manokwari, Indonesia, 2020)
AbstractThis study entitled the effect of learning difficulties on students' cognitive learning achievement on the subject of reaction rates for class XI science at SMA Santo Paul Manokwari. The purpose of this study was to determine the effect of learning difficulties on students' cognitive learning achievement on the subject of reaction rates in class XI IPA at SMA Santo Paulus Manokwari and to find out the relationship between learning difficulties and cognitive learning achievements of students on the subject of reaction rates in class XI IPA in Saint Paul Manokwari High School. This study uses a quantitative method with a descriptive approach. The results of this study indicate that there is a relationship between learning difficulties and students' cognitive learning achievement on the subject of the reaction rate of class XI IPA at SMA Santo Paulus Manokwari of 0.51 while the effect of learning difficulties on cognitive learning achievement is 26.60%. Based on the magnitude of the influence and relationship, it is concluded that learning difficulties have a positive effect on cognitive chemistry learning achievemen.Keywords: Learning Difficulty, Reaction Rate, Quantitative Method, Descriptive Approach and Cognitive Learning Achievement.